Retiring to Spain : Women's Narratives of Nostalgia, Belonging and Community - Ahmed, Anya (Book collections on Project MUSE., 2015)
This title focuses on the lives of a group of women from the UK who moved to the Costa Blanca in Spain in retirement. We follow their journeys as they seek 'community' and belonging in a world characterised by rapid social change. Imbued with nostalgic yearning, community is hailed as a panacea to theills of modernity and as a representation of social continuity.